What’s Mine is Yours : Pilot Evidence from a Randomized Impact Evaluation on Property Rights and Women’s Empowerment in Cote d’Ivoire - Donald, Aletheia; Goldstein, Markus; Hartman, Alexandra; La Ferrara, Eliana; O'Sullivan, Michael; Stickler, Mercedes (World Bank, Washington, DC, 2020)
The protection of formal institutions can help to strengthen women’s property rights, potentially improving welfare and economic efficiency of the household with broader implications. Individual land certification in women’s names and civil marriage registration offer two routes for women towards a more formal delineation of their property rights. In the context of the World Bank Land Policy Improvement and Implementation Project (PAMOFOR), this pilot project examines what drives the take-up of innovative interventions that aim to strengthen women’s property rights in rural Cote d’Ivoire: providing economic incentives for a man to register land in his wife’s name, shifting attitudes through an emotionally resonant video, and encouraging civil marriage in the wake of a new legal reform. Pilot results show how highlighting the benefits of women’s land ownership for family harmony, economic efficiency, and security for the family can induce husbands to reallocate land to their wives.